Aktualisasi Peran Pesantren dalam Mendirikan Baitul Mal Darussalam Syariah sebagai Solusi Problematika Ekonomi Umat - Agus Toni (Al-tsaman : Jurnal Ekonomi dan Keuangan Islam, 2020)
Indonesia, which has the largest Muslim population, should be able to improve the quality of harmonization of a better fellow. Apathy and closed attitudes must be released in order to achieve a mission of the function of Islam as a religion that can cover human life in terms of economic, social and belief. The Islamic values ​​that carry the mission of rahmatan lil alamin become the main foundation in increasing hirrah maximizing the potential to contribute to the success of the government's mission, namely to build a prosperous and civilized society. Islamic boarding schools as a basis and center for the study of religious scholarship should not focus on the applicative form of the theory of worship and faith alone. Tetpi must also be able to answer problems from all lines that are always changing. Such conditions are also the substance of the applicable elements of knowledge learned in everyday life with the concept as codified in the yellow book which is the product of the minds of Muslim scholars or scholars. Islamic boarding schools should be a place for people to seek knowledge and as learning in forming individuals who are able to understand diversity and instill high empathy values ​​for socio-economic relations. Of all the aspects that are needed in dealing with complex problems, it is necessary to have a complete system as the basis for its application by consensus on the value of good management.